Spontaneous heating and gas drainage on a coal face with "four-gateroad" and overlying drainage tunnel - Zhang, M.; Yang, S.; Cheng, Jianwei; Song, W.; Jiao, H.; Zhang, G. (2013)
Based on the 15101 working face, this paper investigates coupling effects between gas drainage and spontaneous heating of residual coal in goaf due to the suction pressure in overlying drainage gateroad in the face with four-gateroad system. Extensive numerical simulations are conducted by setting up the theoretical model, field measurements of boundary conditions and other model parameters. The results show that increasing the negative pressure in overlying drainage gateroad can greatly improve gas drainage efficiency. Methane concentration can also be greatly reduced in the tailgate. The changes of the negative pressure have a little significant effect on the "three-zone" of spontaneous combustion in the gob area. However, if both a high level drainage gateroad and an inner stagger drainage entry exist in the working face, these may lead to significant air leakage in the goaf and consequently increase the risk of combustion heating. The optimum negative pressure can be determined as 2.486 kPa according to the upper gas limit of 2.5% in tailgate in the 15101 working face.